Hukum Suara Wanita Dalam Berpendapat di Ruang Publik (Tinjauan Hadis) - Ramadhan, Muhammad Ardin Abizal (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explore the prophetic traditions (ḥadīths) of Prophet Muhammad ﷺ concerning women’s voices in public spaces, the normative values established by Muslim communities, and the differences between textual interpretations of ḥadīths and evolving societal norms in evaluating women’s vocal presence today. The issue of women’s voices has sparked ongoing debates between textual religious interpretations and modern social dynamics. This research employs a qualitative-descriptive method using a literature study approach, analyzing relevant ḥadīths along with their commentaries found in classical and contemporary Islamic jurisprudence texts. It also examines the sociological development of norms within Muslim communities through a hermeneutic approach. The findings indicate that there is no unanimous scholarly consensus on the ruling regarding women’s voices in public. Some ḥadīths emphasize the importance of modesty and decorum, but do not explicitly prohibit women’s voices altogether. Meanwhile, Muslim Communities form their norms based on cultural interpretation, social necessity, and contemporary developments. This divergence between scriptural understanding and social reality reflects the need for a contextual and dynamic approach to Islamic law, allowing for a more proportionate assessment of women’s vocal participation in public life. This study is expected to contribute to the academic discourse of Islamic thought in a way that supports gender justice and responsiveness to the demands of changing times.